UN Women's Initiatives in Combating Sexual Violence Against Ukrainian Women Amidst the Russia-Ukraine Conflict: English - Amelia Syarif, Rizky; Rosyida, Hamdan Nafiatur (Global Local Interactions: Journal of International Relations, 2024)
The objective of this study is to evaluate the initiatives of UN Women, an organizational entity of the United Nations that specializes in the field of women, in addressing the issues and instances of sexual violence that have been experienced by numerous Ukrainian female civilians as a result of the Russia-Ukraine conflict. This study uses a qualitative descriptive methodology, utilizing sources such as books, journals, news portals, and films. The theory of International Organizations and Sexual assault is employed as a framework to examine the activities of UN Women in addressing instances of sexual assault endured by Ukrainian women as a result of the Russia-Ukraine conflict. The findings indicate that UN Women has implemented numerous initiatives, such as utilizing social media to encourage all segments of society to take action in response to the numerous cases that occur in Ukraine, collaborating with international women's organizations, and addressing the needs of women in the areas of peacebuilding and humanitarian assistance. Additionally, UN Women conducts gender analyses to motivate the entire community to assist in the humanitarian crisis in Ukraine. In addition to psychological support, UN Women offers legal assistance, social service assistance, and aid funds provided by the organization.